Dry etching slurry, preparation method thereof and dry etching method for improving verticality of sidewall of glass-based micro-nano grating array

CN123003153APending Publication Date: 2026-10-30CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610861781.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-15
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

1)导热性能极差,高温下形成显著内部温度梯度,熔体黏度分布严重不均;

Benefits of technology

1、刻蚀速率高

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003153A_ABST
    Figure CN123003153A_ABST
Patent Text Reader

Abstract

The application discloses a dry etching slurry, a preparation method thereof and a dry etching method for improving the verticality of a glass-based micro-nano grating array sidewall, the dry etching slurry comprises, in mass fraction, 5-10 wt% of modified graphene, 3-5 wt% of dimethyl silicone oil, 1-5 wt% of a dispersing agent, 0.04-1 wt% of a pH regulator, and the balance of paraffin wax; the modified graphene is graphene with a porous structure formed by acid etching after an alumina layer with a thickness of 3-10 nm is deposited on the surface of the graphene and ultrasonic dispersion treatment, and the particle size of the graphene is 1-5 mu m; and the pH value of the slurry is 6-8. Through the synergistic effect of the multistage modified graphene and the formula, the heat conductivity, the flowability and the dispersion stability of the slurry are significantly improved, the heat field is uniform in the etching process, the verticality of the glass-based micro-nano grating sidewall and the etching uniformity are effectively improved, the etching rate is stable, the process controllability is strong, and the dry etching slurry is suitable for high-precision micro-nano structure processing and industrialized production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor plasma etching technology, and particularly relates to a dry etching paste and its preparation method, and a dry etching method for improving the sidewall verticality of glass-based micro / nano grating arrays. Background Technology

[0002] Plasma etching is a core process for fabricating glass-based micro / nano grating arrays. It achieves pattern transfer through the physical bombardment and chemical reaction of the sample by plasma. The etching process generates a large amount of heat, and paraffin wax is usually used as a sample binder and thermal buffer material to transfer heat to the tray and cooling system to maintain a stable etching temperature.

[0003] However, traditional pure paraffin materials have a series of defects that have long been difficult to overcome in this field: 1) Extremely poor thermal conductivity, resulting in a significant internal temperature gradient at high temperatures and severely uneven melt viscosity distribution; 2) The flowability is extremely sensitive to temperature. Even a small temperature fluctuation can cause local flow rate differences, making it difficult to cover the sample surface evenly and resulting in uneven heat conduction. 3) Uneven thermal field directly leads to inconsistent thickness of the protective layer on the sidewall of fluorocarbon polymer, and excessive local ion bombardment, causing non-uniform etching; 4) Ultimately, this results in tilted, bent, poorly perpendicular, and low depth uniformity sidewalls of the glass-based micro / nano grating array, failing to meet the requirements of high-precision micro / nano fabrication.

[0004] Current technologies focus on modifying paraffin wax itself or conventional fillers, failing to fundamentally solve the technical bottlenecks of graphene's easy agglomeration, difficulty in constructing thermally conductive networks, and the inability to balance melt flowability and stability. They also lack a complete solution that can simultaneously improve verticality, uniformity, and etching rate. Summary of the Invention

[0005] In view of this, the main objective of the present invention is to provide a dry etching slurry and its preparation method, as well as a dry etching method for improving the verticality of the sidewalls of glass-based micro / nano grating arrays. The technical problem to be solved is to achieve high thermal conductivity, high flowability, and high dispersion stability simultaneously by combining multi-level modified graphene with synergistic formulation and original process, thereby significantly improving the verticality and depth uniformity of the etched sidewalls.

[0006] The objective of this invention and the technical problem it solves are achieved through the following technical solution. This invention proposes a dry etching slurry, comprising, by mass fraction: Modified graphene 5~10wt%, dimethyl silicone oil 3~5wt%, dispersant 1~5wt%, pH adjuster 0.04~1wt%, balance paraffin; The modified graphene is graphene with an aluminum oxide layer deposited on its surface with a thickness of 3-10 nm, which is then acid-etched to form a porous structure and ultrasonically dispersed, and has a particle size of 1-5 μm. The pH value of the slurry is 6-8.

[0007] The objectives of this invention and the technical problems solved can be further achieved by the following technical measures.

[0008] Preferably, in the aforementioned dry etching slurry, the dispersant is selected from sodium methacrylate, sodium dodecylbenzenesulfonate, and polyethylene glycol.

[0009] Preferably, in the aforementioned dry etching slurry, the pH adjuster is selected from one of citric acid, acetic acid, formic acid, sodium hydroxide, and sodium carbonate.

[0010] The objective of this invention and the technical problem it solves are achieved through the following technical solution. This invention proposes a method for preparing a dry etching slurry, comprising the following steps: 1) Graphene is deposited with aluminum oxide with a thickness of 3-10 nm by atomic layer deposition, and then immersed in 0.5-1 mol / L dilute hydrochloric acid for 5-10 min to perform acid etching to create pores. After neutralization, drying and ultrasonic dispersion treatment, the modified graphene is obtained. The molten paraffin and the modified graphene obtained in step 1) are stirred at 90-100℃ and 2000-3000 r / min for 10-20 min to obtain a mixture. 3) While stirring, add dimethyl silicone oil dropwise to the mixture in step 2) at a uniform rate. After the addition is complete, continue stirring at 90~100℃ for 10~20 min. 4) Add dispersant to the material in step 3), stir at 90~100℃ for 20~30 min, then add pH adjuster to adjust the pH value of the system to 6~8, and continue stirring for 5~10 min; 5) Cool and solidify the material obtained in step 4) at 0~10℃ to obtain the dry etching slurry.

[0011] The objectives of this invention and the technical problems solved can be further achieved by the following technical measures.

[0012] Preferably, in the aforementioned method for preparing dry etching slurry, in step 1), the neutralization uses a 1.5~2.5 mol / L sodium hydroxide solution, the drying temperature is 60~80℃, the ultrasonic dispersion frequency is greater than 40 kHz, and the ultrasonic time is 10~20 min.

[0013] Preferably, in the aforementioned method for preparing dry etching slurry, in step 3), the uniform dripping rate of the dimethyl silicone oil is 0.5~2.0 mL / min.

[0014] The objectives of this invention and the technical problems it solves can also be achieved by the following technical measures. This invention proposes a dry etching method for improving the sidewall perpendicularity of a glass-based micro / nano grating array, using the dry etching paste described in any one of claims 1-3, and comprising the following steps: (a) Sample fixation: On a heating stage at 60℃~90℃, the dry etching slurry is coated onto the surface of the sample stage. Then, the glass substrate sample is placed on the slurry, and a pressure of 0.1-0.2MPa is applied to the sample surface and held for 1-3 minutes to allow the sample to bond and fix to the sample stage through the slurry. (b) Dry etching: The sample stage with the sample fixed is sent into the etching equipment chamber, and a mixture of Ar and CHF3 gas is introduced for etching. The flow ratio of Ar to CHF3 is 20:1~10:1, the total gas flow rate is 5-200 sccm, the etching power is 100-300W, the etching pressure is 1-10Pa, and the chamber temperature is 20-40℃. (c) Sample separation: After etching is completed, the sample stage and sample are removed and placed on a heating stage at 60℃~90℃. Then the sample is separated from the sample stage.

[0015] The objectives of this invention and the technical problems solved can be further achieved by the following technical measures.

[0016] Preferably, in the aforementioned dry etching method for improving the sidewall perpendicularity of glass-based micro / nano grating arrays, in step (a), the sample stage is a 2-12 inch single-spray silicon wafer sample stage.

[0017] Preferably, in the aforementioned dry etching method for improving the sidewall verticality of glass-based micro / nano grating arrays, the etching rate using the dry etching paste is 73~77 nm / min.

[0018] Compared with existing technologies, the dry etching paste and its preparation method described in this invention, as well as the dry etching method for improving the sidewall perpendicularity of glass-based micro / nano grating arrays, have the following advantages: 1. High etching rate This invention significantly improves the overall thermal conductivity of the glass substrate during the etching process by introducing highly thermally conductive modified graphene. This allows heat to be rapidly conducted and uniformly diffused within the slurry, significantly accelerating the heat absorption and release rates, effectively shortening the thermal equilibrium time, and thus significantly improving the plasma etching rate. Testing shows that the etching rate of this invention can reach 74~77 nm / min, resulting in a significant improvement in processing efficiency.

[0019] 2. Excellent liquidity This invention, by compounding dimethyl silicone oil and optimizing the component ratio, produces a slurry with excellent wettability and spreading ability after melting. It can form a continuous and flat thermally conductive adhesive layer on the sample surface, avoiding thermal field deviations caused by local uneven thickness, making the etching process more stable and the dimensional control accuracy higher.

[0020] 3. Excellent sidewall verticality This invention enables uniform temperature distribution across the entire etching system, stabilizes the film formation of the fluorocarbon polymer protective layer, and reduces the non-uniform damage to the sidewall protective layer caused by ion bombardment. Actual measurements show that the grating sidewall perpendicularity is stable at 90°~90.1°, with a regular sidewall morphology approaching the ideal perpendicularity.

[0021] 4. Excellent etching uniformity The modified graphene of this invention constructs a continuous and efficient thermally conductive network within the slurry, completely improving the problems of uneven thermal conductivity and localized overheating in traditional paraffin wax, and eliminating hot and cold spots in the sample. The uniformity within and between wafers of this invention can reach 99.8%~99.9%, ensuring highly consistent etching depth and rate, and improving the overall structural consistency of the grating.

[0022] 5. Good substrate compatibility, no secondary pollution. The components of this invention are chemically stable and do not react with the glass substrate, thus preventing scratches or corrosion. After etching, the slurry can be quickly removed by high-temperature melting or solvent cleaning, leaving no residue. This protects the optical performance of the grating and simplifies subsequent cleaning processes.

[0023] 6. Green and environmentally friendly, with high application safety. The slurry of this invention uses only low-toxicity, non-volatile, and biodegradable raw materials, which is different from traditional products containing toxic organic solvents and heavy metals. No harmful waste is generated during the preparation and use stages, which is friendly to operators and the environment and meets the development requirements of green manufacturing.

[0024] 7. The process is simple and easy to mass-produce. The slurry formulation of this invention is clear and the preparation process is simple. It does not require high-end equipment or harsh working conditions. The etching process parameters have a reasonable adjustable range and high stability. It can reduce quality fluctuations caused by human operation, is suitable for industrialized production lines, and effectively control production costs and improve product qualification rate.

[0025] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below. Attached Figure Description

[0026] Figure 1 shows the morphology of the glass-based micro / nano grating array after slurry etching prepared in this invention, with vertical and uniform sidewalls; Figure 2 shows the morphology of a glass-based micro / nano grating array after etching with paraffin material using existing technology, with unevenly tilted sidewalls. Detailed Implementation

[0027] To further illustrate the technical means and effects adopted by the present invention to achieve the intended purpose, the following, in conjunction with preferred embodiments, details the specific implementation, structure, features, and effects of the dry etching paste and its preparation method, and the dry etching method for improving the sidewall perpendicularity of glass-based micro / nano grating arrays proposed according to the present invention. In the following description, different "embodiments" or "embodiments" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable form.

[0028] Unless otherwise specified, all materials and reagents mentioned below are commercially available products well-known to those skilled in the art; unless otherwise specified, all methods described are methods known in the art. Unless otherwise defined, the technical or scientific terms used should have the ordinary meaning understood by those skilled in the art. Where specific experimental steps or conditions are not specified below, they can be performed according to the conventional experimental steps or conditions described in the literature in this field.

[0029] Some embodiments of the present invention provide a dry etching slurry comprising, by mass fraction: Modified graphene 5~10wt%, dimethyl silicone oil 3~5wt%, dispersant 1~5wt%, pH adjuster 0.04~1wt%, balance paraffin; The modified graphene is graphene with an alumina layer of 3-10 nm thickness deposited on its surface, acid-etched to form a porous structure, and ultrasonically dispersed, with a particle size of 1-5 μm. This configuration aims to suppress graphene agglomeration, improve dispersion stability, and retain high thermal conductivity, ensuring uniform dispersion of graphene in the paraffin system and constructing an efficient thermally conductive network to guarantee a uniform etching thermal field. Particle sizes below 1 μm are prone to agglomeration, while those above 5 μm are difficult to disperse uniformly. The acid-etched porous structure and ultrasonic dispersion further balance dispersion stability and thermal conductivity, ensuring etching uniformity and sidewall perpendicularity.

[0030] As the most important material for improving thermal conductivity, the amount of graphene has a decisive and non-linear impact on the thermal conductivity of composite materials. Too much or too little graphene will cause problems, primarily concerning the formation of thermal conduction pathways and interfacial thermal resistance. When the graphene content is less than 5 wt%, it is too low and dispersed within the paraffin matrix, isolated and unconnected. Heat still needs to be transferred slowly through the intermolecules of paraffin; the graphene acts merely as isolated "thermal islands," unable to form rapid thermal conduction paths. Graphene has an extremely high specific surface area and strong van der Waals forces; when the content exceeds 10 wt%, it is too high and easily aggregates. Aggregated graphene forms large particles or flocculents, disrupting the originally intended uniform network.

[0031] The purpose of dimethyl silicone oil is to reduce friction and interaction between graphene molecules, helping them to disperse better in the paraffin matrix, reducing agglomeration, and thus more effectively constructing thermally conductive pathways. It can also directly reduce the viscosity of the entire composite system, improving its flowability. When the content is less than 3 wt%, the amount of silicone oil is insufficient to effectively encapsulate and lubricate the graphene. Graphene agglomerates will become entangled and overlap, forming a robust three-dimensional network structure that greatly hinders the movement of paraffin molecular chains. Even if the paraffin is completely melted, the entire composite material may exhibit a paste-like or even semi-solid gel state, with extremely poor flowability, making it difficult to pour or fill molds. When the content is greater than 5 wt%, the amount of silicone oil is excessive and will fill the spaces between paraffin molecules and graphene, acting as a strong diluent and significantly weakening the interaction forces between paraffin molecular chains and between graphene networks.

[0032] The dispersant (one of sodium methacrylate, sodium dodecylbenzenesulfonate, or polyethylene glycol) aims to form a dense and as thin as possible monomolecular adsorption layer on the graphene surface, thereby achieving stable dispersion while minimizing the negative impact on thermal conductivity. When the content is less than 1 wt%, the dispersion fails, resulting in an overly viscous material that fails to achieve the intended purpose of adding graphene. When the content is greater than 5 wt%, the graphene may still be dispersed, but the excessively thick insulating layer and dilution effect significantly reduce the material's thermal conductivity.

[0033] pH adjusters are used to stabilize the acidity and alkalinity of the system, ensure component compatibility and stable dispersion, and prevent corrosion of the glass substrate. When the content is less than 0.04 wt%, it is too low and cannot effectively stabilize the pH, resulting in poor dispersibility. When the content is greater than 1 wt%, it is too high and can easily lead to phase separation and ion residue contamination of the substrate.

[0034] Paraffin wax serves as a matrix, providing a bond and forming base, and working in conjunction with other components to achieve a balance of performance. Too little paraffin wax will reduce the bond strength and structural stability, while too much will lead to insufficient thermal conductivity and fluidity, affecting the etching effect.

[0035] The pH value of the slurry is 6-8.

[0036] This invention controls the pH value of the dry etching slurry within the neutral range of 6-8. The main purpose is to balance the stability of the slurry system, the compatibility of components, and the etching morphology requirements of the glass substrate, ensuring the sidewall perpendicularity and structural integrity of the glass-based micro / nano grating array. Below pH 6, the system is too acidic, easily causing slight chemical corrosion to the glass silicate substrate, resulting in over-etching at the bottom of the grating, sidewall tilting, and increased roughness. Simultaneously, the acidic environment disrupts the adsorption state of the dispersant on the graphene surface, leading to particle agglomeration and decreased slurry stability. Above pH 8, the system is too alkaline, easily exacerbating the saponification or phase separation of organic components such as paraffin and dimethyl silicone oil, causing stratification and demulsification of the slurry. Furthermore, the alkaline environment increases the etching reactivity on the glass surface, causing uncontrolled etching rates and making it difficult to control the sidewall perpendicularity of the grating. By controlling the pH in the neutral range of 6 to 8, excessive corrosion of the glass substrate by acids and alkalis can be avoided, while maintaining the stability of the dispersion system, ensuring uniform compatibility of each component, making the etching process uniform and controllable, and significantly improving the verticality of the sidewalls of the micro-nano grating array.

[0037] In some optional embodiments, the dispersant may be selected from sodium methacrylate, sodium dodecylbenzenesulfonate, and polyethylene glycol. This dry etching slurry system contains components such as paraffin wax, dimethyl silicone oil, and graphene. The system has problems such as large differences between the solid and liquid phases, easy agglomeration and stratification, and insufficient stability, which significantly affect the uniformity of subsequent etching and the perpendicularity of the grating sidewalls.

[0038] Sodium methacrylate has good ionic dispersion properties and can effectively inhibit the agglomeration of graphene particles through electrostatic repulsion. At the same time, it has moderate compatibility with paraffin and silicone oil systems and does not damage the overall uniformity of the slurry.

[0039] Sodium dodecylbenzenesulfonate, as an anionic surfactant, can significantly reduce the interfacial tension of the slurry, improve the emulsification and dispersion effect of paraffin and dimethyl silicone oil, and enable graphene to be uniformly distributed in the organic phase medium, avoiding uneven etching rate caused by local enrichment.

[0040] Polyethylene glycol is a nonionic dispersant with steric stabilizing properties. It has good compatibility with both polar and nonpolar components and can achieve stable dispersion of paraffin, silicone oil and graphene without introducing too many ionic impurities, reducing the interference of particle deposition on the morphology of the grating sidewalls during the etching process.

[0041] All three dispersants mentioned above can ensure the stability of the slurry while avoiding the introduction of metal ions or complex functional groups that could cause substrate contamination, which is beneficial for improving the sidewall verticality and structural uniformity of glass-based micro / nano grating arrays.

[0042] In some optional embodiments, the pH adjuster may be selected from citric acid, acetic acid, formic acid, sodium hydroxide, and sodium carbonate. These five adjusters can precisely control the pH of the slurry while taking into account the etching selectivity of the glass substrate, the verticality control of the sidewall morphology, and the process stability, thereby reducing impurity residues and structural defects from the source and meeting the high-precision processing requirements of micro / nano grating arrays.

[0043] Some embodiments of the present invention also provide a method for preparing a dry etching slurry, comprising the following steps: 1) Graphene is deposited with 3-10 nm of alumina through atomic layer deposition, then immersed in 0.5-1 mol / L dilute hydrochloric acid for 5-10 min to create pores (forming a porous structure). After neutralization, drying, and ultrasonic dispersion, modified graphene is obtained. Depositing an appropriate alumina film on its surface is also an efficient auxiliary method for surface modification. By significantly weakening the van der Waals attraction between the layers, it fundamentally inhibits agglomeration, greatly reducing the difficulty of graphene dispersion and improving dispersion stability. When the deposition thickness is less than 3 nm, the film is too thin, and due to poor coating uniformity, some graphene is not coated, thus failing to achieve the desired modification effect. When the deposition thickness is greater than 10 nm, the film is too thick, which reduces the thermal conductivity of graphene. Selectively removing some alumina through acid etching can form a porous structure on the graphene surface. On one hand, the residual alumina acts as a "spacer," effectively hindering van der Waals forces between graphene particles and preventing aggregation. On the other hand, the porous structure prevents the film from completely covering the graphene surface, maximizing the preservation of its high thermal conductivity and achieving the dual goals of preventing aggregation and maintaining thermal conductivity. When the concentration is greater than 1 mol / L or the soaking time is longer than 10 min, excessively high hydrochloric acid concentrations or prolonged soaking times can lead to excessively large pore sizes, affecting structural stability and even completely etching away the film. Conversely, when the concentration is less than 0.5 mol / L or the soaking time is less than 5 min, insufficient hydrochloric acid concentrations or prolonged soaking times are ineffective in etching a porous structure, thus failing to prevent aggregation.

[0044] 2) Stir the molten paraffin and modified graphene at 90~100℃ and 2000~3000 r / min for 10~20 min; At speeds below 2000 r / min, the rotation speed is too low to "tear apart" and "disperse" the graphene clumps that have formed secondary agglomerations during mixing. Undispersed graphene clumps will be unevenly distributed within the paraffin matrix, forming obvious aggregation zones and failing to create an effective thermal or electrical conductive network. At speeds above 3000 r / min, the excessive rotation speed generates a large amount of frictional heat, causing a rapid increase in the mixture temperature. This leads to localized overheating of the paraffin or silicone oil, resulting in oxidation, degradation, or cross-linking. Paraffin is the matrix of this system, with a typical melting point between 50-80℃. If the temperature is below 90℃, the stirring temperature is below its melting point, and the paraffin remains solid, unable to mix with other liquid components (dimethyl silicone oil), and unable to provide a dispersible liquid environment for the graphene. Mixing is ineffective; temperatures above 100℃ cause thermal decomposition, producing small-molecule hydrocarbons that lead to discoloration (yellowing, blackening), charring, weight loss, and performance degradation. Furthermore, the methyl groups on the molecular side of dimethyl silicone oil are oxidized, resulting in increased viscosity and even cross-linking and gelation, losing fluidity and affecting final performance. Therefore, a heating temperature of 90-100℃ is chosen. If the stirring time is less than 10 minutes, the molten paraffin does not adequately wet the graphene, making it difficult to completely disperse the graphene particles. This leads to localized agglomeration and uneven distribution, resulting in poor uniformity of the subsequent etching slurry, significant rate fluctuations during etching, and problems such as high roughness and insufficient perpendicularity on the grating sidewalls. If the stirring time is longer than 20 minutes, the combined effects of high temperature and high speed cause the system to easily entrain a large amount of air, forming stable microbubbles that are difficult to remove. Simultaneously, prolonged strong shearing can damage the structural integrity of graphene and may also cause slight thermal oxidation of the paraffin, affecting the overall stability of the slurry and the etching effect, thereby reducing the etching uniformity of the grating array.

[0045] 3) Add dimethyl silicone oil dropwise at a rate of 0.5–2.0 mL / min during stirring, and continue stirring for 10–20 min; The purpose of employing this specific drop rate is to effectively suppress bubble generation within the system while ensuring thorough mixing of dimethyl silicone oil with components such as paraffin and graphene. This avoids phase separation and particle agglomeration caused by sudden changes in local concentration, thereby ensuring the uniformity and stability of the dry etching slurry and providing a reliable foundation for improving the sidewall verticality of the subsequent glass-based micro / nano grating array. If the drop rate is below 0.5 mL / min, the feeding time is too long, significantly reducing production efficiency. Furthermore, prolonged stirring can introduce more air into the system, forming tiny bubbles that are difficult to remove, resulting in defects within the slurry and affecting etching uniformity. If the drop rate is above 2.0 mL / min, a large amount of dimethyl silicone oil rushes in within a short time, easily causing local enrichment and insufficient emulsification. This makes it difficult to disperse quickly and uniformly with paraffin and graphene, forming a distinct phase interface and generating a large number of bubbles, ultimately leading to decreased slurry stability and poor etching consistency.

[0046] After the addition is complete, stirring continues for 10–20 minutes to ensure that the paraffin, dimethyl silicone oil, and graphene components are fully wetted and evenly dispersed. This further removes residual microbubbles from the system, eliminates local concentration gradients, and brings the slurry to a uniform and stable state. This ensures the uniformity of subsequent dry etching and is beneficial for obtaining high-vertical sidewalls in glass-based micro / nano grating arrays. If the stirring time is less than 10 minutes, the system is not fully mixed, graphene is prone to local agglomeration, the paraffin and dimethyl silicone oil interface is not completely fused, and microbubbles cannot be effectively expelled, resulting in poor slurry uniformity. This leads to rate fluctuations during etching and defects such as tilting, roughness, and local over-etching on the grating sidewalls. If the stirring time is longer than 20 minutes, excessive stirring will cause the system to re-enter a large amount of air, forming stable bubbles that are difficult to eliminate. At the same time, prolonged shearing may disrupt the equilibrium of the dispersion system, causing graphene to agglomerate again or the slurry to separate. This not only reduces production efficiency but also decreases the stability of the etching slurry and affects the verticality of the grating array sidewalls.

[0047] 4) Add the dispersant and stir for 20-30 minutes, then add the pH adjuster to adjust the pH to 6-8, and continue stirring for 5-10 minutes. This setting aims to ensure the dispersant is fully adsorbed onto the graphene particle surface, while simultaneously ensuring thorough wetting and uniform dispersion with the paraffin and dimethyl silicone oil system, forming a stable dispersion system. This eliminates particle agglomeration and localized component unevenness, laying the foundation for subsequent pH adjustment and slurry homogenization. If the stirring time is less than 20 minutes, the dispersant will not fully function, graphene is prone to agglomeration, and the system uniformity will be poor, directly affecting the subsequent etching uniformity and grating sidewall perpendicularity. If the stirring time is longer than 30 minutes, excessive air entrainment will easily form stable microbubbles, and excessive shearing may damage the already formed dispersion structure, leading to decreased slurry stability and the occurrence of stratification or particle sedimentation.

[0048] After adding the dispersant, stirring for 20-30 minutes is necessary to ensure the dispersant is fully adsorbed onto the graphene particle surface. This allows the dispersant to break up agglomerated particles through electrostatic repulsion or steric hindrance, while simultaneously ensuring thorough mixing of the dispersant with the molten paraffin and dimethyl silicone oil, forming a stable and homogeneous mixture. This provides a stable foundation for subsequent pH adjustment and slurry formation. If the stirring time is less than 20 minutes, the dispersant may not adequately wet and coat the graphene, resulting in incomplete particle dispersion and agglomeration. This leads to poor slurry uniformity and uneven etching rates, affecting the perpendicularity of the grating sidewalls and surface roughness. If the stirring time exceeds 30 minutes, excessive stirring can introduce a large amount of air, forming stable microbubbles. Furthermore, prolonged high shear may disrupt the established stable dispersion structure, causing slurry stratification, particle re-agglomeration, and reduced preparation efficiency.

[0049] After adjusting the pH to 6-8, continue stirring for 5-10 minutes. This is to ensure the pH adjuster diffuses rapidly and evenly within the system, maintaining a stable overall pH value and avoiding localized pH deviations. It also further removes trace air bubbles, bringing the slurry system to a final homogeneous and stable state. Stirring for less than 5 minutes results in uneven distribution of the pH adjuster, leading to localized pH differences, unstable etching performance, poor grating array morphology consistency, and difficulty in controlling sidewall verticality. Stirring for more than 10 minutes will re-enter air, generating bubbles, disrupting system homogeneity, prolonging the process cycle, and potentially affecting the dispersion system's balance, thus reducing the effectiveness of the etching slurry.

[0050] 5) Cool and solidify at 0~10℃ to obtain the dry etching slurry. Under high-speed stirring, the silicone oil is uniformly distributed in the molten paraffin in the form of extremely small droplets. At this time, the temperature is reduced to allow the paraffin to rapidly crystallize and solidify, locking in this "metastable" uniform structure, thereby obtaining a homogeneous composite material on a macroscopic scale. This results in a dry etching slurry with uniform structure and stable performance, ensuring a uniform etching rate during subsequent etching processes, which is beneficial for the formation of high-verticality sidewalls in glass-based micro / nano grating arrays.

[0051] If the cooling temperature is below 0℃, the excessively low temperature will cause the paraffin to crystallize too quickly, resulting in coarse and uneven grains. This easily generates internal stress and microcracks, making the slurry structure loose. It also easily leads to the freezing of water or low-boiling components in the system, disrupting the slurry's homogeneity and making it difficult to form a uniform film during use, causing etching morphology defects. If the cooling temperature is above 10℃, the cooling rate is too slow, and the paraffin does not solidify in time. The uniformly dispersed silicone oil droplets are prone to aggregation, merging, and phase separation. The metastable structure cannot be effectively locked, leading to macroscopic inhomogeneity and layering problems in the slurry. Etching rate fluctuations are likely to occur, and the perpendicularity and uniformity of the grating sidewalls will significantly decrease.

[0052] In some optional embodiments, step 1) uses a 1.5-2.5 mol / L sodium hydroxide solution for neutralization, the drying temperature is 60-80℃, the ultrasonic frequency is >40 kHz, and the ultrasonic time is 10-20 min. Drying removes residual moisture from the graphene, allowing for better dispersion in subsequent processes. Temperatures below 60℃ are too low and will result in incomplete drying; temperatures above 80℃ will cause uneven heating, leading to significant differences in film shrinkage, resulting in film rolling, warping, and twisting. Ultrasonic time shorter than 10 min is too short, causing some graphene to remain unevenly dispersed, leading to agglomeration, uneven thermal conductivity, poor etching verticality, and etching inhomogeneity. Ultrasonication for 10-20 min is sufficient to achieve dispersion saturation; time longer than 20 min is too long and has no effect on subsequent processes.

[0053] The purpose of using this concentration of sodium hydroxide solution for neutralization is to quickly and thoroughly neutralize the residual dilute hydrochloric acid from the pore-forming process, achieving a neutral environment in the system. This prevents residual acidic groups from damaging the stability of subsequent etching slurries and also prevents acid residue from corroding the glass substrate, ensuring the verticality and morphological integrity of the micro / nano grating sidewalls. Concentrations below 1.5 mol / L: The alkali concentration is too low, resulting in a slow and incomplete neutralization rate. A large number of hydrogen ions remain in the system, which can easily lead to a low pH in the slurry, abnormal charge state on the graphene surface causing aggregation, and acid residue can corrode the glass substrate, resulting in rough and tilted grating sidewalls. Concentrations above 2.5 mol / L: The alkali concentration is too high, easily causing localized over-alkaliness, resulting in excessive etching of the alumina layer on the graphene surface, damaging the porous structure. High-concentration alkali also introduces excessive sodium ions, easily causing glass substrate contamination, affecting the accuracy of the grating structure, and increasing the burden and cost of subsequent water washing.

[0054] An ultrasonic frequency greater than 40 kHz was selected for dispersion to utilize the cavitation and shearing effects of high-frequency ultrasound to finely disperse the agglomerated modified graphene, enabling it to fully exfoliate and form a stable monodisperse system without damaging the graphene itself or its surface alumina porous structure, thus ensuring uniform distribution in the subsequent slurry. Ultrasonic frequencies below 40 kHz are too low, resulting in excessive cavitation intensity and strong impact, which can easily cause mechanical damage to the graphene sheets and surface alumina porous structure, compromising the pore-forming effect. Furthermore, low-frequency ultrasound dispersion lacks uniformity, allowing graphene to still easily agglomerate, affecting etching uniformity. While ultrasonic frequencies above 40 kHz offer milder cavitation, reduced penetration and insufficient dispersion energy prevent effective disassembly of graphene agglomerates, leading to incomplete dispersion. Additionally, excessively high frequencies increase equipment energy consumption and can easily cause localized overheating, resulting in graphene structural defects.

[0055] In some optional embodiments, the stirring temperature in steps 3) to 4) is 90-100°C. The purpose is to keep the system in a molten paraffin state, ensuring the slurry has suitable fluidity, while also ensuring the dispersant, pH adjuster, and all components are fully compatible. This avoids uneven mixing due to paraffin solidification and a sudden increase in system viscosity caused by excessively low temperatures; it also prevents damage to the graphene structure, volatilization of dimethyl silicone oil, and thermal oxidation of paraffin caused by excessively high temperatures. If the stirring temperature is below 90°C, the paraffin's fluidity deteriorates, its viscosity increases, and the components are difficult to mix fully, easily leading to graphene agglomeration and slurry stratification, affecting etching uniformity. If the stirring temperature is above 100°C, dimethyl silicone oil is easily lost through volatilization, and high temperatures can cause thermal aging and oxidative deterioration of the paraffin, damaging the slurry's stability and potentially damaging the graphene structure, reducing etching precision.

[0056] Before etching, set the etching gas mixture of Ar and CHF3 with a flow ratio of 20:1 to 10:1, and control it between 5-200 sccm. The etching power is 100-300W, the etching pressure is 1-10Pa, the equipment chamber temperature is controlled at 20-40℃, and the machine is preheated for 20-40 minutes in advance.

[0057] The Ar to CHF3 flow ratio is set to 20:1~10:1: CHF3, as a reactive gas, can dissociate to generate F radicals, achieving chemical etching of the SiO2 dielectric layer and ensuring high etching efficiency; Ar, as an inert gas, provides physical bombardment ions, which on the one hand increases the etching rate, and on the other hand opens the microstructure of the SiO2 surface, removes CFx polymers generated during the etching process, and avoids excessive corrosion of the photoresist by excessive F radicals, ensuring the etching selectivity between the photoresist and SiO2, and ensuring that the sidewalls of the etched pattern are vertical, without obvious undercuts or cone angles. When the ratio is less than 10:1 (i.e., CHF3 is excessive), too many F radicals are generated by the dissociation of CHF3, causing a sharp increase in the SiO2 etching rate; at the same time, the amount of CFx polymer deposition increases, causing the sidewalls of the etched pattern to become coarser and polymer residues to remain at the bottom, resulting in poor etching uniformity; the etching selectivity between the photoresist and SiO2 decreases significantly, the photoresist is over-etched, rounded corners appear at the top, and even defects such as undercuts and lateral etching occur, resulting in distorted etched patterns. When the ratio is greater than 20:1 (i.e., CHF3 is insufficient), the chemical etching effect is weakened and the etching rate drops significantly. The proportion of physical bombardment by Ar ions is too high, resulting in incomplete etching of the SiO2 dielectric layer. At the same time, ion damage is enhanced, the roughness of the sidewalls of the etched pattern increases, and defects such as micro-masking, pinholes, and uneven etching are prone to occur, affecting device performance.

[0058] Maintaining the total flow rate between 5 and 200 sccm ensures a stable gas replacement rate within the etching chamber, uniform distribution of the reactive gas, and controllable etching pressure. This avoids issues such as insufficient flow rate leading to the inability to promptly remove contaminants and reaction byproducts, and excessive flow rate resulting in gas waste, excessive vacuum pump load, and pressure runaway. When the total flow rate is less than 5 sccm: the gas renewal rate within the chamber is too slow, preventing timely removal of contaminants and reaction byproducts generated during etching, leading to etching rate drift and extremely poor etching uniformity within and between wafers; simultaneously, plasma stability decreases, making flashover and flameout more likely, causing etching process interruptions. When the total flow rate is greater than 200 sccm: the vacuum pump load is excessive, leading to unstable etching pressure control and pressure surges; gas utilization decreases, increasing etching costs; simultaneously, excessively high gas velocity causes uneven local airflow distribution within the chamber, further exacerbating the poor etching uniformity problem.

[0059] The etching power is controlled between 100 and 300 W to provide sufficient energy for the dissociation of the etching gas, enabling Ar and CHF3 to effectively dissociate into ions and free radicals. Simultaneously, controlling the ion bombardment energy achieves anisotropic etching of the SiO2 dielectric layer, ensuring the perpendicularity of the etched pattern. This avoids problems such as slow etching rate and poor anisotropy due to excessively low power, and photoresist damage and substrate ion implantation damage due to excessively high power. When the power is less than 100 W, the plasma dissociation is insufficient, and the ion energy is too low, resulting in an extremely low etching rate that cannot meet mass production efficiency requirements. At the same time, insufficient ion bombardment capability leads to poor etching anisotropy, tilted sidewalls of the etched pattern, and defects such as incomplete etching, bottom residue, and microburrs. When the power exceeds 300 W, the ion energy is too high, which can cause severe etching, thinning, or even cracking of the photoresist, making it unable to effectively protect the underlying dielectric layer. At the same time, the substrate (such as Si or SiN layers) will be damaged by ion implantation, affecting the electrical performance of the device. The increased roughness of the sidewalls and bottom trenches of the etched pattern may also cause charge damage, leading to device failure.

[0060] The etching pressure is controlled between 1 and 10 Pa. This pressure range falls within the low-to-medium pressure zone, ensuring that the mean free path of the ions is within a reasonable range, giving the ions good directionality and thus achieving vertical etching. Simultaneously, it balances the ratio of chemical reaction to physical bombardment, avoiding slow etching rates and poor uniformity due to excessively low pressure, and enhanced lateral etching due to excessively high pressure. When the pressure is less than 1 Pa, the mean free path of the ions is too long and the directionality is too strong, easily leading to over-etching and damage to the underlying material. At the same time, the plasma density decreases, the etching rate slows down, and the etching uniformity deteriorates. Furthermore, it places extremely high demands on the vacuum pump's vacuum level, making it difficult for ordinary etching equipment to maintain this pressure stably, thus reducing its practicality. When the pressure is greater than 10 Pa, the number of ion collisions within the chamber increases, and the ion directionality deteriorates. The etching mechanism changes from anisotropic to isotropic, resulting in enhanced lateral etching, larger sidewall cone angles in the etched pattern, and severe linewidth loss. Simultaneously, reaction byproducts are difficult to remove, leading to a large amount of CFx polymer deposition within the chamber, further affecting the etching quality.

[0061] The cavity temperature is controlled between 20 and 40°C: This maintains stable temperatures for the etching cavity, electrodes, and walls, preventing poor etching repeatability caused by temperature fluctuations; it also suppresses the condensation of moisture and residual solvents, reduces abnormal CFx polymer deposition, and ensures stable etch pattern morphology. Preheating for 30 minutes allows the cavity to reach thermal equilibrium, eliminates the first-wafer effect, ensures consistency of etching parameters for each wafer, and avoids abnormal etching rate and uniformity on the first wafer. When the temperature is below 20°C, moisture and residual solvents in the cavity easily condense on the cavity walls and wafer surface, leading to poor etching repeatability; CFx polymers are more likely to deposit on the sidewalls of the etch pattern, causing abnormal morphology; at the same time, large temperature differences at different locations in the cavity lead to decreased etching uniformity within and between wafers. When the temperature is above 40°C, the photoresist softens, deforms, or even flows, causing etch pattern distortion and linewidth drift; the wafer is subjected to thermal stress, making it prone to warping; abnormal CFx polymer volatilization leads to drift of the etching endpoint, making it impossible to accurately control the etching depth.

[0062] When preheating is not performed or the preheating time is less than 30 minutes, the cavity wall temperature and electrode temperature do not reach thermal equilibrium, resulting in a severe first-wafer effect. The etching rate, uniformity, and pattern morphology of the first etched wafer are all significantly abnormal. The water vapor remaining in the cavity will react with the etching gas to produce substances such as H2O and HF, which will damage the etched structure and equipment components.

[0063] Some embodiments of the present invention also provide a dry etching method for improving the sidewall perpendicularity of a glass-based micro / nano grating array. In the dry etching process, the above-mentioned dry etching paste is used to bond and fix the glass-based sample to a 2-12 inch sample stage on a heating stage at 60°C to 90°C. When fixing the sample, a pressure of 0.1-0.2 MPa needs to be gently applied to the sample surface and maintained for 1-3 minutes, while keeping the temperature of the heating stage constant, and then the sample enters the cavity for etching.

[0064] After etching is complete, turn off the etching gas and etching power. Open the chamber, remove the sample stage and sample, and place them on a heating stage at 60℃~90℃. Then, gently separate the sample from the sample stage.

[0065] During etching, the dry etching paste achieves uniform heat conduction and thermal buffering, aiming to stabilize the etching temperature field, reduce local overheating, and ensure etching anisotropy and consistency. This results in a sidewall perpendicularity of 90±0.1° and intra-wafer / inter-wafer uniformity ≥99.8% for the glass-based micro / nano grating array. A perpendicularity of 90±0.1° ensures regular grating sidewalls without significant tilt, meeting device optical performance requirements. A perpendicularity below 89.9° is prone to sidewall inclination and pattern distortion, while a perpendicularity above 90.1° is prone to sidewall outclination and undercut failure. Uniformity ≥99.8% ensures consistent etching depth both intra-wafer and inter-wafer, improving product yield; below 99.8%, significant etching differences occur, leading to decreased performance stability.

[0066] During dry etching, glass substrate samples are bonded and fixed to 2-12 inch staged on a heating stage at 60-90℃. This ensures the dry etching paste is in a suitable softened and bonded state, guaranteeing a tight and secure fit between the sample and stage while preventing paste flow and sample displacement due to excessive temperature. If the temperature is below 60℃, insufficient paste softening and weak adhesion result in unreliable sample fixation, making displacement during etching more likely, leading to grating morphology shifts and dimensional deviations. If the temperature is above 90℃, excessive paste softening and flow cause uneven bonding layer thickness. High temperatures also facilitate thermal migration of paste components, affecting heat conduction uniformity and resulting in poor sidewall perpendicularity. For samples smaller than 2 inches, the stage area is too small, making sample installation and positioning difficult, resulting in poor clamping and heating uniformity, which fails to meet the mounting requirements of conventional micro / nano fabrication. When the size is greater than 12 inches, the stage is too large and is prone to thermal warping and reduced surface flatness. It is difficult to ensure uniform thermal field across the entire area, which will reduce the etching uniformity and sidewall perpendicularity consistency of large-area samples.

[0067] Applying a pressure of 0.1 MPa to 0.2 MPa in this step aims to ensure a tight fit between the glass substrate sample and the stage, eliminating air gaps at the interface and guaranteeing uniform heating and stable heat conduction during etching. This, in turn, helps improve the perpendicularity of the micro / nano grating array sidewalls. Simultaneously, it enhances the adhesion of the dry etching paste, preventing sample displacement, warping, or even detachment within the vacuum chamber. If the pressure is below 0.1 MPa, the sample will not adhere tightly to the stage, potentially leading to uneven heat transfer, variations in etching rates, and decreased perpendicularity of the grating sidewalls. Furthermore, it poses a risk of weak adhesion and sample displacement. If the pressure exceeds 0.2 MPa, it can easily cause microcracks or even breakage in the glass substrate, and may also cause deformation of the micro / nano grating structure under pressure, affecting pattern accuracy.

[0068] Applying pressure for 1 to 3 minutes aims to ensure that the dry etching slurry is fully wetted and evenly spread under heating conditions, forming a stable and reliable bonding layer, eliminating interfacial stress, and ensuring that the sample remains fixed during subsequent vacuuming and etching processes. If the holding time is less than 1 minute, the slurry will not be fully wetted and set, resulting in insufficient bonding strength and making the sample prone to loosening and shifting. If the holding time exceeds 3 minutes, the slurry may age and become brittle due to excessive heating time, which not only increases the difficulty of subsequent separation but may also introduce additional thermal stress, affecting the grating morphology and dimensional consistency.

[0069] Using the aforementioned dry etching paste enables uniform heat conduction and thermal buffering during the etching process, avoiding localized heat concentration that could cause differences in etching rates. This ensures that the sidewall perpendicularity of the glass-based micro / nano grating array reaches 90±0.1°, and the intra-wafer / inter-wafer uniformity is ≥99.8%. If the perpendicularity deviates from the 90±0.1° range, falling below the lower limit or exceeding the upper limit, it will cause the grating sidewalls to tilt, resulting in abnormal optical performance, decreased diffraction efficiency, and failure to meet the requirements for micro / nano device use. If the intra-wafer / inter-wafer uniformity is below 99.8%, the etching depth and linewidth differences in different areas will be too large, resulting in poor grating array consistency and severely affecting device performance stability and yield.

[0070] In some optional embodiments, the sample stage is a single-polished silicon wafer sample stage. The purpose of selecting a single-polished silicon wafer as the sample stage is to utilize its high surface flatness, low roughness, uniform thermal conductivity, and stable coefficient of thermal expansion. This allows for close bonding with the dry etching paste at a bonding temperature of 60℃ to 90℃, ensuring uniform bonding layer thickness and consistent thermal conduction between the glass substrate sample and the sample stage. This results in a uniform temperature field distribution during etching, effectively improving the sidewall perpendicularity and inter-wafer uniformity of the glass substrate micro / nano grating array.

[0071] In some optional embodiments, the etching rate using the dry etching paste is 73–77 nm / min. Controlling the dry etching rate at 73–77 nm / min aims to ensure efficient glass-based micro / nano grating fabrication while achieving precise control over the etching process. This ensures a stable match between etching energy and material removal rate, preventing grating sidewall tilting, bottom over-etching, or morphological distortion caused by rate fluctuations. This also guarantees a sidewall perpendicularity of 90 ± 0.1° and maintains high intra- and inter-wafer uniformity. If the etching rate is less than 73 nm / min, the etching process is too slow, resulting in a significant reduction in production efficiency. Long-term etching can easily lead to photoresist layer aging and edge wear, which in turn can cause distortion of the grating linewidth. At the same time, the etching ions stay on the sidewalls for too long, which can easily cause lateral etching to intensify and the sidewall verticality to decrease. If the etching rate is greater than 77 nm / min, the etching reaction is too violent and the ion bombardment energy is too high, which can easily cause uncontrolled etching of the glass substrate, resulting in problems such as local over-etching, bottom taper, and sidewall roughness. At the same time, the excessively fast rate can lead to significant heat accumulation and uneven heat distribution, which can further damage the uniformity of the grating structure and make it impossible to guarantee high verticality and high consistency.

[0072] In the above technical solution, the present invention first performs atomic layer deposition coating on graphene and then forms a porous structure through acid etching and ultrasonic high-intensity vibration dispersion. Then, using paraffin as a base, it combines graphene with extremely high thermal conductivity and dimethyl silicone oil with good fluidity to make the slurry, thereby improving the thermal conductivity of the slurry and achieving the effect of improving the verticality and depth uniformity of the etched sidewalls.

[0073] The present invention will be further described below with reference to specific embodiments, but this should not be construed as a limitation on the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention still fall within the scope of protection of the present invention. Example 1

[0074] This embodiment provides a dry etching slurry, which comprises the following components by mass fraction: 79 wt% paraffin wax; 10 wt% graphene with a particle size of 1 μm; 5 wt% dimethyl silicone oil; 5 wt% sodium methacrylate; 1 wt% acetic acid; and a pH value of 8.0.

[0075] The preparation method of the above-mentioned dry etching slurry includes the following steps: First, graphene was placed in an atomic layer deposition apparatus to deposit a 3 nm thick alumina film using a reaction of trimethylaluminum and water. The reaction temperature was 150 °C, the source pulse time was 0.5 ms, the nitrogen flow rate was 500 sccm, and the purging time was 10 s. After deposition, the film was immersed in 0.5 mol / L dilute hydrochloric acid for 10 minutes; then neutralized with 1 mol / L sodium hydroxide solution, and dried in an oven at 60 °C; finally, it was dispersed using ultrasound at a frequency of 40 kHz for 10 minutes.

[0076] Paraffin and graphene were mixed at 3000 r / min and 100 °C. The mixture was stirred for 20 min, then dimethyl silicone oil was added and stirred for another 20 min. Sodium methacrylate was added and stirred for another 30 min. Citric acid was added to adjust the pH to 8.0, and the mixture was stirred for another 10 min. Finally, the mixture was cooled to 10 °C and solidified to obtain the material with improved etching uniformity.

[0077] The dry etching paste prepared above is used for dry etching of glass-based micro / nano grating arrays. The specific steps are as follows: Preparation before etching: Set the etching gas to a mixture of Ar and CHF3 with a flow ratio of 20:1, where the Ar flow rate is 5 sccm and the CHF3 flow rate is 0.25 sccm; set the etching power to 100W, the etching pressure to 1Pa, and the equipment cavity temperature to 20℃, and preheat the machine for 30 minutes in advance. Sample fixation: On a heating stage at 60°C, the glass substrate sample is bonded and fixed to the 2-inch single-sided polished silicon wafer stage using the above-mentioned dry etching paste. A pressure of 0.1 MPa is applied to the sample surface and held for 1 minute, while the temperature of the heating stage is kept constant. Cavity etching: The sample stage with the sample fixed is sent into the etching cavity, and dry etching is performed according to the above-mentioned set parameters. The etching rate is 73 nm / min. Sample separation: After etching is completed, the etching gas and etching power are turned off, the cavity is opened, the sample stage and sample are taken out and placed on a heating stage at 60°C. Then the sample and sample stage are gently separated to obtain the finished glass-based micro / nano grating array. Example 2

[0078] This embodiment provides a dry etching slurry, which comprises the following components by mass fraction: 90.96 wt% paraffin wax; 5 wt% graphene with a particle size of 5 μm; 3 wt% dimethyl silicone oil; 1 wt% sodium methacrylate; 0.04 wt% acetic acid; and a pH value of 6.0.

[0079] The preparation method of the above-mentioned dry etching slurry includes the following steps: First, graphene was placed in an atomic layer deposition apparatus to deposit a 10 nm thick alumina film using a reaction of trimethylaluminum and water. The reaction temperature was 150 °C, the source pulse time was 0.5 ms, the nitrogen flow rate was 500 sccm, and the purging time was 10 s. After deposition, the film was immersed in 1 mol / L dilute hydrochloric acid for 5 minutes; then neutralized with 2 mol / L sodium hydroxide, and finally dried in an oven at 80 °C. Finally, the film was dispersed using ultrasound at a frequency of 40 kHz for 10 minutes.

[0080] Paraffin and graphene were mixed at 2000 r / min and a stirring temperature of 90°C. The mixture was stirred for 10 min, followed by the addition of dimethyl silicone oil. The mixture was stirred for another 10 min, then sodium dodecylbenzene sulfonate was added and stirred for 20 min. Sodium carbonate was added to adjust the pH to 6.0, and the mixture was stirred for another 5 min. Finally, the mixture was cooled to 0°C to solidify and obtain the material with improved etching uniformity.

[0081] Preparation before etching: Set the etching gas to be a mixture of Ar and CHF3 with a flow ratio of 15:1, where the Ar flow rate is 100 sccm and the CHF3 flow rate is about 6.7 sccm; set the etching power to 200W, the etching pressure to 5Pa, and the equipment cavity temperature to 30℃, and preheat the machine for 30 minutes in advance. Sample fixation: On a heating stage at 75°C, the glass substrate sample was bonded and fixed to a 6-inch single-sided polished silicon wafer stage using the above-mentioned dry etching paste. A pressure of 0.15 MPa was applied to the sample surface and held for 2 minutes, while the temperature of the heating stage was kept constant. Cavity etching: The sample stage with the sample fixed is sent into the etching cavity, and dry etching is performed according to the above-mentioned set parameters. The etching rate is 75 nm / min. Sample separation: After etching is completed, the etching gas and etching power are turned off, the cavity is opened, the sample stage and sample are taken out and placed on the heating stage at 75°C. Then the sample and sample stage are gently separated to obtain the finished glass-based micro-nano grating array. Example 3

[0082] The difference between this embodiment and Embodiment 1 is that the modified graphene content in this embodiment is 8 wt%, the paraffin content is 81 wt%, and the remaining components, steps, and parameters are the same as in Embodiment 1. Example 4

[0083] The difference between this embodiment and Embodiment 1 is that the graphene particle size in this embodiment is 3 μm, while the other components, steps and parameters are the same as in Embodiment 1. Example 5

[0084] The difference between this embodiment and Embodiment 1 is that the thickness of the alumina layer in this embodiment is 6 nm, while the other components, steps and parameters are the same as in Embodiment 1. Example 6

[0085] The difference between this embodiment and Embodiment 1 is that the concentration of dilute hydrochloric acid in this embodiment is 0.8 mol / L, while the other components, steps and parameters are the same as in Embodiment 1. Example 7

[0086] The difference between this embodiment and Embodiment 1 is that the dimethyl silicone oil content in this embodiment is 4 wt%, the paraffin content is 80 wt%, and the remaining components, steps, and parameters are the same as in Embodiment 1. Example 8

[0087] The difference between this embodiment and Embodiment 1 is that the dispersant in this embodiment is sodium dodecylbenzenesulfonate, while the other components, steps, and parameters are the same as in Embodiment 1. Example 9

[0088] The difference between this embodiment and Embodiment 1 is that the pH of the slurry in this embodiment is adjusted to 7.0, while the other components, steps and parameters are the same as in Embodiment 1.

[0089] Example 10 The difference between this embodiment and Embodiment 1 is that the stirring speed in this embodiment is 2500 r / min, while the other components, steps and parameters are the same as in Embodiment 1.

[0090] Example 11 The difference between this embodiment and Embodiment 1 is that the cooling temperature in this embodiment is 5°C, while the other components, steps, and parameters are the same as in Embodiment 1.

[0091] Comparative Example 1 The difference between this comparative example and Example 1 is that the concentration of dilute hydrochloric acid in this comparative example is 5 mol / L, while the other components, steps and parameters are the same as in Example 1.

[0092] Comparative Example 2 The difference between this comparative example and Example 1 is that the drying temperature of this comparative example is 100°C, while the other components, steps and parameters are the same as in Example 1.

[0093] Comparative Example 3 The difference between this comparative example and Example 1 is that the graphene particle size in this comparative example is 0.1 μm, while the other components, steps and parameters are the same as in Example 1.

[0094] Comparative Example 4 The difference between this comparative example and Example 1 is that the graphene content in this comparative example is 3 wt%, the paraffin content is 86 wt%, and the remaining components, steps, and parameters are the same as in Example 1.

[0095] Comparative Example 5 The difference between this comparative example and Example 1 is that the dimethyl silicone oil content in this comparative example is 2 wt%, the paraffin content is 82 wt%, and the remaining components, steps and parameters are the same as in Example 1.

[0096] Comparative Example 6 The difference between this comparative example and Example 1 is that the sodium methacrylate content in this comparative example is 8 wt%, the paraffin content is 82 wt%, and the remaining components, steps, and parameters are the same as in Example 1.

[0097] Comparative Example 7 The difference between this comparative example and Example 1 is that the dimethyl silicone oil in this comparative example is poured in directly in one go, while the other components, steps and parameters are the same as in Example 1.

[0098] Comparative Example 8 The difference between this comparative example and Example 1 is that in this comparative example, the dispersant is added first and then the dimethyl silicone oil is added, while the other components, steps and parameters are the same as in Example 1.

[0099] Comparative Example 9 The difference between this comparative example and Example 1 is that no dispersant is added in this comparative example, while the other components, steps and parameters are the same as in Example 1.

[0100] Comparative Example 10 The difference between this comparative example and Example 1 is that the stirring speed in this comparative example is 1000 r / min, while the other components, steps and parameters are the same as in Example 1.

[0101] Comparative Example 11 The difference between this comparative example and Example 1 is that the thickness of the alumina layer in this comparative example is 20 nm, while the other components, steps and parameters are the same as in Example 1.

[0102] Application method: The slurry prepared in Examples 1-11 and Comparative Examples 1-11 was used to uniformly coat and bond the glass sample to the 8-inch single-sided polished silicon wafer stage on a heating stage at 75°C.

[0103] Test methods: Scanning electron microscopy was used to test the surface structure dimensions of the samples. Twenty samples were uniformly placed on a silicon wafer, and five points were sampled for each sample. The uniformity within and between wafers was calculated, and the perpendicularity of the sidewalls of the micro / nano gratings was measured. The test results of Examples 1-11 and Comparative Examples 1-11 are shown in Table 1.

[0104] Table 1

[0105] As can be seen from Table 1, the etching rate of Examples 1 to 11 of the present invention is 74 to 77 nm / min, the intra-wafer uniformity is 99.8 to 99.9%, the inter-wafer uniformity is 99.8 to 99.9%, and the perpendicularity is 90° to 90.1°.

[0106] As can be seen from Examples 1-11 and Comparative Examples 1-11, the graphene coating thickness and the mass ratio of each raw material in the etching slurry prepared by this invention exhibit a significant synergistic effect. Specifically, paraffin wax and highly thermally conductive modified graphene effectively enhance the system's thermal conductivity and reduce interfacial thermal resistance. Combined with dimethyl silicone oil, dispersant, and pH adjuster, the components achieve thorough physical fusion, resulting in a stable system with consistent heating rate and temperature uniformity. This system not only firmly fixes the sample during etching but also ensures uniform heat transfer, thereby guaranteeing uniform etching. The etching rate of this invention is stably controlled at 73-77 nm / min, with inter- and intra-sheet uniformity maintained above 99.8%, and the verticality of the glass-based micro / nano grating sidewalls is consistently maintained at 90±0.1°. This significantly improves both the etching rate and uniformity while substantially enhancing the verticality of the grating sidewalls. Furthermore, adjusting the graphene content, particle size, coating thickness, acid etching concentration, dimethyl silicone oil dosage, dispersant type, slurry pH, stirring speed, or cooling temperature can all maintain excellent etching performance, fully demonstrating that the technical solution of this invention has a wide range of applications, a large process window, and strong reproducibility.

[0107] As can be seen from Example 1 and Comparative Example 8, the order of material addition has a significant impact on the particle suspension stability, which in turn affects the etching rate and uniformity. The preferred order of adding paraffin, graphene, dimethyl silicone oil, dispersant, and pH adjuster in this invention can significantly improve the dispersion stability of the system, thereby improving the etching rate and etching uniformity.

[0108] As can be seen from Examples 1-11 and Comparative Example 9, the absence of a dispersant leads to a decrease in the dispersion uniformity of each component, thereby reducing the etching uniformity. The present invention significantly improves the dispersion uniformity of the multi-component system by adding a specific dispersant, maintaining its uniform stability at over 99.8%.

[0109] As can be seen from Example 1 and Comparative Example 7, the present invention uses a method of uniformly dripping dimethyl silicone oil, which, compared to adding it directly at once, avoids the generation of bubbles and local agglomeration due to slow dispersion speed and insufficient mixing, resulting in more uniform material mixing and significantly improving etching uniformity.

[0110] As can be seen from Example 1 and Comparative Example 10, using a stirring speed of 2000~3000 r / min, compared with 1000 r / min, can more effectively disperse agglomerated particles, improve mixing efficiency and uniformity, reduce air bubbles in the system, and further improve etching uniformity.

[0111] Each comparative example exhibited varying degrees of performance degradation due to deviations from the scope of this invention in a single parameter or step. Comparative Examples 1-3 and 11 primarily suffered from abnormal graphene modification-related parameters, leading to impaired graphene dispersion and structural integrity, which in turn affected heat conduction and etching uniformity. Comparative Examples 4-6 experienced decreased stability and fluidity of the slurry system and insufficient etching precision due to deviations in component content. Comparative Examples 7-8 suffered from uneven mixing, bubbles, or stratification due to incorrect addition methods and sequences. Comparative Example 9 exhibited the worst etching effect due to severe graphene agglomeration caused by a lack of dispersant. Comparative Example 10 failed to meet performance standards due to insufficient stirring speed and inadequate component mixing.

[0112] In summary, this invention, by controlling the graphene content to 5-10 wt%, dimethyl silicone oil to 3-5 wt%, and dispersant to 1-5 wt%, and coordinating with specific preparation processes (such as dropwise addition of dimethyl silicone oil and high-speed stirring), ensures the effective functioning of each component and the stability and homogeneity of the system, which is key to achieving high etching performance. The component content, preparation steps, and parameter selections in Example 1 are all optimal solutions, and their mutual cooperation achieves homogeneous and stable slurry, thereby ensuring high verticality and high uniformity of the glass-based micro / nano grating array after dry etching, solving the technical problem of poor etching effect in existing etching slurries.

[0113] Numerous specific details are set forth in this specification. However, it will be understood that embodiments of the invention may be practiced without these specific details. In some embodiments, well-known methods, structures, and techniques have not been shown in detail so as not to obscure the understanding of this specification.

[0114] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0115] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

[0116] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.

Claims

1. A dry etching slurry, characterized in that, Including by mass fraction: Modified graphene 5~10wt%, dimethyl silicone oil 3~5wt%, dispersant 1~5wt%, pH adjuster 0.04~1wt%, balance paraffin; The modified graphene is graphene with an aluminum oxide layer deposited on its surface with a thickness of 3-10 nm, which is then acid-etched to form a porous structure and ultrasonically dispersed, and has a particle size of 1-5 μm. The pH value of the slurry is 6-8.

2. The dry etching slurry as described in claim 1, characterized in that, The dispersant is selected from sodium methacrylate, sodium dodecylbenzenesulfonate, and polyethylene glycol.

3. The dry etching slurry as described in claim 1, characterized in that, The pH adjuster is selected from one of citric acid, acetic acid, formic acid, sodium hydroxide, and sodium carbonate.

4. A method for preparing the dry etching slurry according to any one of claims 1-3, characterized in that, Includes the following steps: 1) Graphene is deposited with aluminum oxide with a thickness of 3-10 nm by atomic layer deposition, and then immersed in 0.5-1 mol / L dilute hydrochloric acid for 5-10 min to perform acid etching to create pores. After neutralization, drying and ultrasonic dispersion treatment, the modified graphene is obtained. 2) The molten paraffin and the modified graphene obtained in step 1) are stirred at 90~100℃ and 2000~3000 r / min for 10~20 min to obtain a mixture. 3) While stirring, add dimethyl silicone oil dropwise to the mixture in step 2) at a uniform rate. After the addition is complete, continue stirring at 90~100℃ for 10~20 min. 4) Add dispersant to the material in step 3), stir at 90~100℃ for 20~30 min, then add pH adjuster to adjust the pH value of the system to 6~8, and continue stirring for 5~10 min; 5) Cool and solidify the material obtained in step 4) at 0~10℃ to obtain the dry etching slurry.

5. The method for preparing the dry etching slurry as described in claim 4, characterized in that, In step 1), the neutralization uses a 1.5~2.5 mol / L sodium hydroxide solution, the drying temperature is 60~80℃, the ultrasonic dispersion frequency is greater than 40 kHz, and the ultrasonic time is 10~20 min.

6. The method for preparing the dry etching slurry as described in claim 4, characterized in that, In step 3), the uniform dropping rate of the dimethyl silicone oil is 0.5~2.0 mL / min.

7. A dry etching method for improving the sidewall perpendicularity of a glass-based micro / nano grating array, characterized in that, Using the dry etching slurry according to any one of claims 1-3, and comprising the following steps: (a) Sample fixation: On a heating stage at 60℃~90℃, the dry etching slurry is coated onto the surface of the sample stage. Then, the glass substrate sample is placed on the slurry, and a pressure of 0.1-0.2MPa is applied to the sample surface and held for 1-3 minutes to allow the sample to bond and fix to the sample stage through the slurry. (b) Dry etching: The sample stage with the sample fixed is sent into the etching equipment chamber, and a mixture of Ar and CHF3 gas is introduced for etching. The flow ratio of Ar to CHF3 is 20:1~10:1, the total gas flow rate is 5~200 sccm, the etching power is 100~300W, the etching pressure is 1~10Pa, and the chamber temperature is 20~40℃. (c) Sample separation: After etching is completed, the sample stage and sample are removed and placed on a heating stage at 60℃~90℃. Then the sample is separated from the sample stage.

8. The dry etching method for improving the sidewall perpendicularity of a glass-based micro / nano grating array as described in claim 7, characterized in that, The sample stage is a 2-12 inch single-displacement silicon wafer sample stage.

9. The dry etching method for improving the sidewall perpendicularity of a glass-based micro / nano grating array as described in claim 7, characterized in that, The etching rate using the dry etching slurry is 73~77 nm / min.

10. The dry etching method for improving the sidewall perpendicularity of a glass-based micro / nano grating array as described in claim 7, characterized in that, The verticality of the sidewalls of the dry-etched glass-based micro / nano grating array is 90±0.1°, and the intra-chip / inter-chip uniformity is ≥99.8%.